Environmental and human health implications of metal(loid)s: Source identification, contamination, toxicity, and sustainable clean-up technologies - Kumar, Pankaj; Gacem, Amel; Ahmad, Mohammad Tauheed; Yadav, Virendra Kumar; Singh, Snigdha; Yadav, Krishna Kumar; Alam, Md Mottahir; Dawane, Vinars; Piplode, Satish; Maurya, Parul; Ahn, Yongtae; Jeon, Byong-Hun; et al. (Frontiers in Environmental Science, 2022)
Environmental pollution is becoming more prevalent in both human life and the ecosystem. The increased use of fossil fuels, mining, and the burning of wastes, as well as industrial wastewater discharge, are polluting natural resources such as water, soil, and air. Metals(loid)s (Cu, Cr, Cd, Zn, Ni, Pb, Hg, Sb, Sn, and As) contribute to several ecological problems when exposed to humans and the environment resulting in serious health and environmental risks. The pollution of aquatic and terrestrial sites with these elements is an issue of environmental as well as public health significance. The present review highlights environmental problems instigated by the toxic metal(loid)s, their source, and respective health/environmental concern along with the importance of creating low-cost, environmentally acceptable clean-up technologies for treating household and industrial wastewater. Various physical, chemical, biological, and/or biochemical as well as their various combinations have been described from the sustainable technological point of view. Techniques such as ion exchange, membrane filtration, photocatalysis, bioremediation, phytoremediation, economical biosorbents, and nanomaterials have been discussed in detail along with respective recent case studies to gain a significant inside towards the solution of the environmental problems focused and action-oriented sustainable technologies development. Thus, this article significantly provides a deep insight into metal(loid)s toxicity, source identification, and their influences on the ecosystem and human health along with conventional and sustainable clean-up technologies